Municipal Statistics 1998-99 Directorate of Economics & Statistics Bangalore Government of Karnataka - Planning Commission (Planning Commission, 1998)
In Karnataka State, the history of urban local self-governing bodies dates back to more than a century. In common terminology they are known as “Municipalities” and have been constituted mainly to serve/fulfil the basic public amenities viz., (a) supply of potable water (b) operation and maintenance of drainage and sewerage systems (c) providing public lighting (d) maintaining sanitary conditions and hygiene of public places (e) construction and maintenance of bus terminals, roads, culverts and bridges (f) maintenance of public parks and gardens (g) ensuring systematic urban growth (h) regulation of building construction and (I) licensing of commercial activities. Depending upon resources, they also undertake educational, health, community and recreational services. Of late, their sphere of activity has been extended to implementation of special programmes for the urban poor and down trodden.
Directorate of Economics & Statistics Bangalore Government of Karnataka